Radiation Dose Distribution Measurements of Kilo-Voltage Photons Using Optically Stimulated Luminescence Detectors (OSLs) in Radiological Procedures - Syed Mansoor Naqvi; Zaheer Uddin; Zafar Sajjad; Imran Ahmed Siddiqui; Amjad Hussan (Journal of Basic & Applied Sciences, 2016)
OSL detectors were used for dose measurement in a solid water phantom. Two other detectors, Cobia Flex (RTI Electronics) and PTW-Diados were also used to verify the measurements. Radiation doses were measured for a wide range of radiographic techniques and set of parameters from very low (1 mAs, 55 kV) to very high (140 mAs, 120 kV) exposures. Multiple x-ray units were used to ensure that the measured doses are independent of x-ray units and are dependent on the specified radiographic parameters. Measurements were performed at the standard medical radiographic imaging Source-to-Image-Distances (SID) of 100 cm and 180 cm. all the x-ray beams were collimated to produce a 20 cm × 20 cm field size. We measured the radiation doses at different depths and estimated entrance surface doses during common radiological procedures. Measured doses fall exponentially with depths at all energies and exposures. A nonlinear relation is clearly evident between the dose and the x-ray beam energy. The measurements also show that the radiation dose is directly proportional to the exposure. Entrance Surface Doses (ESD) were also measured and found to be as low as 0.119 mGy±0.020 (0.092-0.141) for extremities to as high as 13.083 mGy±3.988(8.246-17.560) to the Spine and Abdomen. ESDs for the chest x-ray were measured to be 0.158 mGy±0.074(0.034-0.275).